Current state of equipment for phototherapy in institutions of dermatovenereologic profile - Elena Yu. Novoselova; Margarita R. Rakhmatulina; Arfenya E. Karamova (State Scientific Center of Dermatovenereology and Cosmetology, 2023)
Background. The use of phototherapy for the treatment of dermatoses and lymphoproliferative disease is determined by the Procedure for rendering assistance in the field of "dermatovenereology" and clinical guidelines approved by the Scientific and Practical Council of the Ministry of Health of Russia. Foreign-made medical equipment for phototherapy occupies a key position in Russia, the equipment of medical organizations with it is more than 75%. However, in the current reality, foreign companies not only raise prices for the export of medical equipment, but also stop its supply and service in Russia, which may adversely affect the quality of medical care. Aims. To assess the current state of the technical support of medical organizations of the dermatovenereological profile with equipment for phototherapy of dermatoses. Materials and methods. Information about the availability of equipment for phototherapy of dermatosis and/or the need to purchase it, the intensity of use of the available equipment for various nosologies, as well as problems related to its service, obtained from 64 medical organizations of the dermatovenerological profile in 62 constituent entities of the Russian Federation. The initial data collected as a result of the survey were structured, unified and brought to a general form using the functionality of the Microsoft Excel program. Further processing of information was carried out using descriptive statistics methods. Results. 8 (12%) specialized medical organizations are currently not equipped with phototherapy equipment. In 56 medical organizations using phototherapy equipment, the share of foreign-made medical equipment is 84%. Of the 22 models of medical equipment, only 12 (54%) are included in the State Register of Medical Devices and have a valid registration certificate. 192 (75%) pieces of equipment of medical organizations are intended for local phototherapy in the medium-wave (UVB) or long-wave (UFA) ultraviolet radiation mode, and only 63 (25%) units are represented by ultraviolet cabins (57 UVA (PUVA) and UVB-311 cabins). and 6 UVA (PUVA) and UVB (SFT) booths). Out of 57 UV cabins, only 18 (32%) are simultaneously equipped with UVA and UVB-311 radiation sources. Half of the medical organizations of the dermatovenereological profile (50%) experience difficulties with servicing the installed devices, 43 (67%) medical organizations reported the need for equipment for phototherapy of dermatosis. Conclusions. Due to the instability of logistics and sanctions for the supply of medical equipment to the country, the development and registration of a medical device for phototherapy of dermatosis and T-cell lymphomas of the skin, and its further production in Russia, is relevant.